Degeneracy of Majorana bound states and fractional Josephson effect in a dirty SNS junction. (15th July 2016) - Ikegaya, S; Asano, Y
Abstract: We theoretically study the stability of more than one Majorana fermion appearing in a p -wave superconductor/dirty normal metal/ p -wave superconductor junction in two-dimensions by using the chiral symmetry of a Hamiltonian. At the phase difference across the junction φ being π, we will show that all of the Majorana bound states in the normal metal belong to the same chirality. Due to this pure chiral feature, the Majorana bound states retain their high degree of degeneracy at zero energy even in the presence of a random potential. As a consequence, the resonant transmission of a Cooper pair via the degenerate Majorana bound states carries the Josephson current at φ = π − 0 +, which explains the fractional current-phase relationship discussed in a number of previous papers.